Neurorehabilitation of social dysfunctions: a model-based neurofeedback approach for low and high-functioning autism - Pineda, Jaime A.; Friedrich, Elisabeth V. C.; LaMarca, Kristen (Frontiers in Neuroengineering, 2014)
Autism Spectrum Disorder (ASD) is an increasingly prevalent condition with core deficits in the social domain. Understanding its neuroetiology is critical to providing insights into the relationship between neuroanatomy, physiology and social behaviors, including imitation learning, language, empathy, theory of mind, and even self-awareness. Equally important is the need to find ways to arrest its increasing prevalence and to ameliorate its symptoms. In this perspective, we highlight neurofeedback studies as viable treatment options for high-functioning as well as low-functioning children with ASD. Specifically, we focus on neurofeedback interventions combined with other kinds of behavioral conditioning to induce neuroplastic changes that can address the full spectrum of the autism phenotype.